Twenty-five rice research priorities for sustainable rice systems by 2050 - Edwards, Glory I.; Nelson, Katherine; le Clec'h, Solen; Luu, Tang; Coast, Onoriode; Futakuchi, Koichi; Kok, Kasper (Cambridge University Press, 2024)
Non-technical Summary: Agricultural research is vital for sustainable food production, amid changing challenges. To address these challenges effectively and achieve sustainable food systems, researchers and funding bodies have to prioritize research efforts. We conducted horizon scanning to determine how rice systems might change by 2050 and to identify key research gaps. The study involved 101 rice experts from 31 countries who rated the research gaps based on novelty and relevance. The top 25 research gaps encompass sustainability, agricultural development, rice crop science (including genetics, breeding, and physiology), and policies. Addressing these research gaps will contribute toward the sustainability of rice systems.